OBM Geriatrics 2020
DOI: 10.21926/obm.geriatr.2002114
|View full text |Cite
|
Sign up to set email alerts
|

Using a Rocking Chair in the Care of People with Dementia: A Single-Case Research Study

Abstract: The people with dementia experience a progressive loss of cognition, while more than 90% of them develop behavioral and psychological symptoms of dementia (BPSD). BPSD may result in physical injuries and psychological distress among people with dementia and their family/caregivers. First-line care strategies in dementia care should not unthinkingly involve pharmacological interventions to avert or reduce the behavior, and should rather consider the person and their unique requirements. Therefore, a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The results of a repeated-measures study revealed that the use of a glider significantly improved emotions and relaxation in people with severe dementia admitted to nursing homes [15]. In the same line, findings from a study using a rocking chair showed a decrease in BPSD and an increase in quality of life in PWD in a nursing home [16]. In a multicenter survey of long-term care facilities staff reported the use of a rocking chair improved quality of care and contributed to a calmer environment for PwD [17].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The results of a repeated-measures study revealed that the use of a glider significantly improved emotions and relaxation in people with severe dementia admitted to nursing homes [15]. In the same line, findings from a study using a rocking chair showed a decrease in BPSD and an increase in quality of life in PWD in a nursing home [16]. In a multicenter survey of long-term care facilities staff reported the use of a rocking chair improved quality of care and contributed to a calmer environment for PwD [17].…”
Section: Introductionmentioning
confidence: 84%
“…Based on the methodology used in previous studies, we consider that a frequency of three times per week would be adequate to study the effect of the NSC on BPSD [14][15][16][17]. A research team from the Instituto Andaluz de Neurociencia (four neuropsychologists and one psychiatrist) filled the outcomes measures of the study results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several programmes for motion and music. The chairs are developed for relaxation and reverse the negative behaviour in patients with neuropsychiatric symptoms, during dementia disease 12 …”
Section: Methodsmentioning
confidence: 99%
“…The chairs are developed for relaxation and reverse the negative behaviour in patients with neuropsychiatric symptoms, during dementia disease. 12 Patients allocated to the intervention group will receive a daily minimum of 20 min of rocking therapy. The music will be turned on, unless the patient declines music.…”
Section: Rocking Chair Therapy (Intervention Group)mentioning
confidence: 99%